INNOVATIVE ACTIVITY AS A FACTOR OF INCREASING ECONOMIC DEVELOPMENT - Ergashev Akmaljon (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study explores the role of innovative activity as a critical driver of economic development, focusing on the integration of global scientific achievements and innovations to foster growth in various sectors, particularly startups. Method: A comprehensive analysis of contemporary innovation practices was conducted, combining theoretical reviews and case studies of successful international examples. The study also examines the intersection of creativity and technological advancements as foundational elements of innovation. Results: The findings demonstrate that innovation significantly contributes to economic stability and growth by enhancing productivity, promoting entrepreneurial ventures, and fostering sustainable development. Startups, in particular, benefit from a structured approach to adopting innovative practices, leading to societal and economic advancements. The study highlights the importance of integrating foreign experiences and adapting them to local contexts for optimal outcomes. Novelty: This research offers a fresh perspective on the centrality of artistic creativity as a foundation for innovation and emphasizes the strategic importance of startups in the innovation ecosystem. It bridges the gap between global practices and local implementation, providing actionable insights for policymakers and entrepreneurs aiming to enhance economic resilience through innovation.